In situ characterization of crystallization and melting of soft, thermoresponsive microgels by small-angle X-ray scattering. Issue 8 (7th January 2022) - Lapkin, Dmitry; Mukharamova, Nastasia; Assalauova, Dameli; Dubinina, Svetlana; Stellhorn, Jens; Westermeier, Fabian; Lazarev, Sergey; Sprung, Michael; Karg, Matthias; Vartanyants, Ivan A.; Meijer, Janne-Mieke
Abstract : By combining thermoresponsive core–shell gold–PNIPAM microgels with USAXS, the crystallization and melting of soft colloidal crystals is investigated in detail with Bragg peak analysis. Abstract : Depending on the volume fraction and interparticle interactions, colloidal suspensions can form different phases, ranging from fluids, crystals, and glasses to gels. For soft microgels that are made from thermoresponsive polymers, the volume fraction can be tuned by temperature, making them excellent systems to experimentally study phase transitions in dense colloidal suspensions. However, investigations of phase transitions at high particle concentration and across the volume phase transition temperature in particular, are challenging due to the deformability and possibility for interpenetration between microgels. Here, we investigate the dense phases of composite core–shell microgels that have a small gold core and a thermoresponsive microgel shell. Employing Ultra Small-Angle X-ray Scattering, we make use of the strong scattering signal from the gold cores with respect to the almost negligible signal from the shells. By changing the temperature we study the freezing and melting transitions of the system in situ . Using Bragg peak analysis and the Williamson–Hall method, we characterize the phase transitions in detail. We show that the system crystallizes into an rhcp structure with different degrees of in-plane and out-of-plane stacking disorder that increase upon particle swelling. We further find that the melting process is distinctly different, where the system separates into two different crystal phases with different melting temperatures and interparticle interactions.